Pengaruh Sistem Penilaian Kinerja Terhadap Kinerja Karyawan Finance Department di Petrochina International Companiesi in Indonesia - Ismulyana Djan; Mimpi Retnowati (Jurnal Ilmiah Binaniaga, 2007)
Basically the company’s performance is a very important thing. Without good performance it is unlikely that a company can reach its target and predetermined objective. The purpose of this research is to know the influence of performance evaluation system on employees’ performance. The proposed hypothesis is “It is assumed that performance evaluation system has a significant influence on employee’s performance in Finance Department”. The independent variable (X) was performance evaluation system while dependent variable (Y) was employee’s performance, where the value of X on Y was 0.500.